Incidence, etiopathogenesis and pathological aspects of genitourinary tuberculosis in India: A journey revisited - Prasenjit Das; Arvind Ahuja; Siddhartha Datta Gupta (Indian Journal of Urology, 2008)
Background: Tuberculosis is one of the major health problems in India. Genitourinary tuberculosis comprises 20% of all extrapulmonary tuberculosis, and is the most common extrapulmonary system to be affected by this disease. The recent surge in the incidence of HIV-infected patients in India has further ignited the fury. Though the members of the Mycobacterium species are well identified, the incidence could not be controlled due to its complex etiopathogenesis and genetic background. Pathological Spectrum: The spectrum of pathological changes of genitourinary tuberculosis is wide, which varies from normal morphology to markedly scarred kidney, bladder, and epididymis with autocystectomy. A thorough knowledge is required to prevent the end-stage complications. The sequel can be detrimental for the patient′s physical, behavioral, psychological, and financial health. Diagnostic Dilemmas: Though culture and polymerase chain reaction are available for the detection of tuberculosis, the sensitivity and specificity varies widely and one should be aware. Conclusions: A thorough knowledge of epidemiology, immunopathogenesis, spectrum of the disease and the possible sequels, will help better and effective management of the disease.